The Development of Animation-Based Digital Learning Media to Increase Learning Interest among Elementary School Students - Rahmawati Patta; Amir Pada; Meinarti (Sains Global Institut, Indonesia, 2026)
This study employed a literature review method aimed at examining the effect of developing animation-based digital learning media on improving elementary school students' interest in learning. Animation-based learning media has emerged as an educational innovation capable of creating a more engaging, interactive, and enjoyable learning environment. The study was conducted by collecting and analyzing relevant scientific journal articles published within the last five years. The findings indicate that the use of animation-based media can enhance students' motivation, attention, and interest during the learning process. Furthermore, animation media helps students understand learning materials more effectively through attractive visual displays, audio elements, and moving images. In addition, the implementation of animation-based digital media enables teachers to create more creative and innovative learning experiences, encouraging students to participate actively in classroom activities. Therefore, the development of animation-based digital learning media is highly important for implementation in elementary school education.